ANALISA KINERJA RUAS JALAN IMAM BONJOLDAN SIMPANG JALAN IMAM BONJOL – JALAN DAYA NASIONAL DI KOTA PONTIANAK - Saldi, Angga Prialiadi; AS, Syafaruddin; Kadarini, S. Nurlaily (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Road plays an important role in transportation activities and population mobility. The high activity at the intersection of Jalan Imam Bonjol - National Power Road causes a traffic flow conflict. So that it needs an analysis of the performance of Jalan Imam Bonjol and the intersection of Jalan Imam Bonjol - Jalan Daya Nasional in order to provide improvements to the problems of road and intersection performance. This study primary data collection in the form of a survey of road and intersection traffic volume, road geometric and intersection, and road side barriers on Friday, Saturday, Sunday, and Monday at 06.00 - 21.00 and secondary data, namely location maps, population and vehicles in Pontianak City . Then the data is analyzed traffic volume in units of junior high / hour followed by calculation of road capacity to the degree of traffic saturation, calculating road performance for the next 5 years and calculating intersection traffic volume, intersection capacity and degree of saturation for signalless and signaled intersections. Based on the results of the analysis it is known that the degree of saturation of Jalan Imam Bonjol = 0.90. In the year 2022 degrees of saturation = 1.12, while for the intersection of Jalan Imam Bonjol - National Power Road the degree of saturation is = 1.70. With the high degree of saturation, the geometric improvements in roads and intersections need to be done to increase capacity. On Jalan Imam Bonjol widening the road to 12 meters with 4 lanes 2 directions so that the degree of saturation = 0.59 and in 2022 degrees saturation = 0.73. The high degree of saturation at the intersection requires that the settings using traffic lights get the degree of saturation = 1.08. The still high degree of saturation requires a geometric change in the intersection of Jalan Imam Bonjol - Jalan Daya Nasional, on Jalan Imam Bonjol with a width of 12 meters with 4 lanes 2 directions and at Daya National Road with a width of 10 meters with 2 lanes 2 directions so that the degree of saturation is obtained = 0.87. Alternative repairs carried out are using traffic lights with 2 phases, degree of saturation = 0.74 with delay = 19 seconds / second where the level of intersection performance (c) traffic flow is still stable, and transferring vehicles from the National Power Road to the Road Imam Bonjol to turn left directly through the BRI office of Tanjungpura University towards the road of the old Post Office of Tanjungpura University.Keywords: Jalan Imam Bonjol, Degree Of Saturation, Road Performance, Intersection Performance